2016
DOI: 10.21071/az.v65i249.446
|View full text |Cite
|
Sign up to set email alerts
|

Replacement value of rumen liquor fermented cassava peels for maize in growing rabbit diet

Abstract: The nutritive potential of rumen liquor fermented cassava peels (RLFCP) was assessed in rabbit nutrition in an 8 weeks trial. The freshly collected droppings from layers were sundried, ground and mixed at 100 g/kg with ground cassava peels, sprayed with rumen filtrate and fermented for 144 hours. Thereafter, one basal diet was formulated to meet the nutrient requirement of a growing rabbit. The maize content (43 g/100 g) of the basal diet was replaced at 0, 25, 50, 75 and 100 % with RLFCP and named as diets 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 11 publications
7
19
1
Order By: Relevance
“…In this study, while the weight gain of the rabbits decreased by 18.96-25.24%, the FCR decreased by 21.76-26.61% as the MFCSR without enzyme supplementation in the diets increased from 0% to 75% and 100%, thus further confirming that beyond 50% replacement level of maize with MFCSR the weight gain vis-à-vis feed utilization by the rabbit will decline. The plausible reason for this observed decline in the weight changes and FCR could be as a result of the cumulative effect of the residual HCN in MFCSR as earlier reported (Oloruntola et al, 2016). In cyanide poisoning, cya- Means with different superscripts in the same row are significant (P<0.05).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this study, while the weight gain of the rabbits decreased by 18.96-25.24%, the FCR decreased by 21.76-26.61% as the MFCSR without enzyme supplementation in the diets increased from 0% to 75% and 100%, thus further confirming that beyond 50% replacement level of maize with MFCSR the weight gain vis-à-vis feed utilization by the rabbit will decline. The plausible reason for this observed decline in the weight changes and FCR could be as a result of the cumulative effect of the residual HCN in MFCSR as earlier reported (Oloruntola et al, 2016). In cyanide poisoning, cya- Means with different superscripts in the same row are significant (P<0.05).…”
Section: Discussionsupporting
confidence: 58%
“…The weekly weight gain, feed consumption, feed conversion ratio, haematological and serum biochemical indices were obtained as described in the paper I (Oloruntola et al, 2018) and by Oloruntola et al (2016). In brief, the weight gain was calculated as the difference between the initial and final weight while the feed consumption was the difference between the feed given and feed left over.…”
Section: Response Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of low animal protein intake (8-15 g per day) in most African and Pacific countries (Ogunsipe et al 2017b) has been associated with rise in cost of animal protein beyond the affordable level by the people in these regions (Oloruntola et al 2016). The increase in price of conventional feed ingredients constitutes the primary cause of the rise in animal feed production cost and the subsequent observed high and unaffordable cost of animal protein (Adeyeye et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is referred to as the African food reserve. Utilization of its peels (5-15% of tuber weight) in monogastric feeding has been advocated as it has the direct benefit in reducing feeding cost and solving the problem of cassava peel disposal (Oloruntola, Agbede, Onibi, & Igbasan, 2016). It was reported that dried cassava peels can be introduced at 30% in balanced rations of growing rabbits as the energy source to replace the corresponding amount of maize grain (Agunbiade et al, 1999;Oloruntanyan, Ayoola, Fayeye, Olagunju, & Olorunsanya, 2007;Omole, 1990).…”
Section: Introductionmentioning
confidence: 99%